Social Deixis in English and Tae' Bastem: Revisting Brown and Gilman's TU and VOS Forms - Nasriandi Nasriandi; Jusriati Jusriati; Syahrir Syahrir (Wanastra: Jurnal Bahasa dan Sastra, 2020)
This research is attempt to discovers the TU and VOS forms in Tae’ Bastem language and in English, TU and VOS  form was first discovered by Brown and Gilman in 1960. TU represents the pronoun that is used in informal/familiar situation and VOS is used in a formal/polite situation. However, the writer sees that TU and VOS is cultural and it will differ from culture to culture. The researcher found TU and VOS forms in Tae’ Bastem, in fact there are six second person pronoun found in Tae’ Bastem,pronoun pronoun “ki”, and “ta”,    pronoun “ki”, and “ta” are used in formal situation or in polite speech, and pronoun “ko” and “mu” are used in informal or impolite speech. Another finding that the writer found is in Tae’ Bastem, there are two pronoun which are used in both situation, whether in informal or formal, polite or impolite speech, which are the pronoun “mi” and “kun”, pronoun “mi” and “kun”  are used in polite or impolite speech. Otherwise, TU and VOS are not found in English, even in the southern English in America, the only second person pronoun which exist in English is “YOU” , and it is used both in formal/informal or polite/impolite situation. However English speaker, especially those who live in southern part of the United states of America, they have their own way in order to distinguish utterances in formal or informal, in formal situation or in polite speech which are; to say “please” when asking for something, to say “thank you” before or after, saying “yes ma’am” “no ma’am”, soft spoken, maintaining eye contact, and even always be aware of voice tone.Keywords: Brown and Gilman, TU and VOS forms, second person pronoun